Real Life vs. Virtual Life: Big Five Personality Traits, Facebook Use and Leisure Activity Engagement - Serra Çelebi (Selçuk İletişim)
The popularity of using Facebook (FB) is widespread among all generations all around the world. This study investigates connections between FB use, leisure activity engagement, and personality traits. Older users’ FB usage was more intensive than younger users’, confirming that FB is aging as well as its users’ age. Frequent and longer hours FB users found less time to see their relatives and friends. But at the same time, those who spend more time with their relatives and friends and less time with FB are the ones who had a high number of FB friends. This may be because of a firm connection between online and offline friendship. Extraverts and agreeable people had a high number of FB friends, but preferred spending times with their relatives and friends instead of being connected to FB online. Consequently, intensive FB usage resulted in less leisure activity engagement.